Intrinsic aging in mixed-cation lead halide perovskites - Minussi, Fernando B. [UNESP]; Bertoletti, Eduardo M. [UNESP]; Eiras, José A.; Araújo, Eudes B. [UNESP] (Royal Society of Chemistry (RSC), 2022)
Among the several characteristics for which halide perovskites (HPs) are recognized, their (in)stability is one main topic of numerous research fronts, which seeks to enable their long-term application in different devices. Many routes for degradation by environmental stressors (light, humidity, oxygen, temperature, etc.), and strategies to mitigate them are known. However, studies involving intrinsic changes these materials can undergo are still scarce in the literature. Among the few reported, those that stand out are related to thin films and devices, in which the presence of additional layers possibly alters the way the HPs change over time. In turn, thermodynamic studies are not in consensus about the intrinsic (in)stability of these systems, and even if they were, other changes could occur beyond those predicted by the known degradation routes. This work studies the temporal aging of the physical properties of the system methylammonium lead iodide (MAPbI3) partially substituted by guanidinium. Using an aging procedure in the dark under controlled humidity and temperature for more than 4000 hours, we demonstrate changes in their structural and microstructural parameters. These changes are much less pronounced in mixed compositions than in pure MAPbI3. While the band gap energy remains constant for all compositions, pure MAPbI3 changes ionic conductivities, relaxation times, intrinsic charge carrier and trap densities, and carrier mobility. Shedding light on the subject, the findings are relevant for developing strategies to achieve more stable and efficient optoelectronic devices for long-term applications.